Didikan Allah Kepada Bangsa Israel Menurut Kitab Hakim-Hakim - Yosia Belo (STT Pelita Dunia, 2019)
Abstract: The Book of Judges is a book that is paradoxical. Because in it there are several historical stories of the Israelites starting from the most famous and also the ones that are not well known. The book of Judges contains many interesting things, but also maybe a lot more disgusting things that the Israelites had done at that time, such as idolatry, adultery, civil war, mixed marriage, and so on. The teaching is simple, but difficult to understand, because in the book of Judges it shows the darkest sins of mankind, but in it the light of God's grace can be seen clearly. Based on the description above, teaching that comes from God is very necessary. It was useful to lead the Israelites on the right path or to bring the Israelites back to their God, who had freed them from slavery in Egypt and also gave them the land of Canaan as an inheritance. This article is an analysis and literature study, which describes some of the ways that God used to educate the Israelites who were corrupted by sin to become Israelites who obeyed God's Law. Abstrak: Kitab Hakim-hakim adalah kitab yang bersifat paradoks. Oleh karena di dalamnya terdapat beberapa cerita sejarah bangsa Israel mulai dari yang paling terkenal serta yang juga yang tidak terkenal. Kitab Hakim-hakim mengandung banyak hal menarik, akan tetapi juga mungkin lebih banyak hal yang menjijikkan yang pernah dilakukan oleh bangsa Israel pada zaman itu, seperti penyembahan berhala, perzinahan, perang saudara, kawin campur, dan sebagainya. Pengajarannya sederhana, akan tetapi sulit untuk dimengerti, karena dalam kitab Hakim-hakim ini memperlihatkan dosa manusia yang paling hitam pekat, tetapi di dalamnya cahaya rahkmat Allah dapat dilihat dengan jelas. Berdasarkan uraian di atas, maka pengajaran yang bersumber dari pada Allah sangat diperlukan. Berguna untuk membawa bangsa Israel kepada jalan yang benar atau membawa kembali bangsa Israel kepada Allah mereka, yang telah membebaskan mereka dari perbudakan di Mesir serta juga memberikan tanah Kanaan kepada mereka sebagai milik pusaka. Artikel ini adalah sebuah analisis dan studi pustaka, yang memaparkan beberapa cara yang Allah gunakan untuk mendidik bangsa Israel yang telah rusak karena dosa menjadi bangsa Israel yang taat terhadap Taurat Tuhan.